Blue Tourism: Treating Marine Ecosystems and Increasing The Potential of Maritime Tourism in Indonesia - Supriyanto, Eko Eddya (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2022)
Blue tourism is a tourism concept based on maritime but coupled with a sustainable governance model. This paper aims to examine the blue tourism literature using the method used to prepare a literature study. This literature study is used to develop the concept of blue tourism, especially in Indonesia. The governance model of Indonesian marine resources has not been carried out optimally, and many challenges are faced in optimizing the potential of coastal tourism in Indonesia. The concept of blue tourism can be used as a model for implementing coastal tourism in Indonesia. The arrangement of the blue tourism concept can start from the essential things, such as providing awareness to residents and travelers to maintain the marine ecosystem in tourist sites so that the resources in tourism locations experience a cycle of sustainability